(untitled) (Journal Of Educational and Psychological Researches, 2013)
Today we are witnessing huge scientific and technical progress so we need more skills and methods of thinking that needs to be acquired by the teacher, as the importance of computers in education there are many teachers suffering of the difficulty in teaching for pupils . researchers tried to find a good suitable way with the technological interests for now which represent by computer design software and the introduction of enrichment activities in the curriculum because it is one of a contemporary trends for the development of the Arabic language with various levels of education and knowing if this program has negative or positive impact. So researchers presented the research Effectiveness of enrichment activities through using software program for second graders in Conversation article with null hypothesis which research sample reached to (60) students in a intentional way distributed into two groups ( experimental group and the control group ) and the researchers used anterior and posterior test , who prepared the appropriate statistical means for research, results showed that there are presence of statistically significant differences between anterior and posterior test in performance and achievement between the experimental group and the control group that went to experimental group which has studied the use of a software program.